Wilhelm Flitner (1889 - 1990) - ein Klassiker der Erziehungswissenschaft? Zur 125. Wiederkehr seines Geburtstags - Nicolaysen, Rainer (Hamburger Universitätsreden Neue Folge, 2015)
On 20 August 2014, Wilhelm Flitner's birthday (1889-1990) was celebrated for the 125th time. On this occasion, the Faculty of Education of the University of Hamburg held a ceremony on October 22, 2014. The talks given during the ceremony are documented in this volume.